Vertical profile of aerosol characteristics including activation over a rain shadow region in India. (1st October 2021) - Varghese, Mercy; Jose, Jerry; Anu, A.S.; Konwar, Mahen; Murugavel, P.; Kalarikkal, Nandakumar; Deshpande, Medha; Prabha, Thara V.
Abstract: Unique airborne observations of aerosol size spectral and chemical characteristics over the peninsular Indian region are illustrated in this case study. Multimodal lognormal distributions were required to fit the observed in situ aerosol size distribution. The aerosol composition and mixing state was deduced from the single-particle analyses of aerosols using the transmission electron microscope and soot photometer coupled with satellite retrieved aerosol classification, and back trajectory analyses. Organic carbon was the most prominent aerosol type found at all altitudes. Refractory black carbon aerosols which constituted about 10–12% of the aerosols in the boundary layer were primarily internally mixed with both inorganic and organic coating. Other major aerosol types were dust and sea salt, with the latter primarily found below 2 km. Further, the cloud forming ability of in-situ aerosols is tested through a cloud condensation nuclei closure analysis. The effective hygroscopicity decreased above cloud base due to the absence of sea salt aerosols. The change in large-scale winds with altitude affected the aerosol composition and hygroscopicity. The multimodal aerosol size distribution and hygroscopicity parameter (κ = 0.18) obtained for the cloud base aerosols over the rain shadow region are useful for studying aerosol-cloud interactions using regional cloud-resolving models. Highlights: Vertical profile of aerosol size distribution and composition from in-situ observations. Internally mixed marine aerosols present in the boundary layer over rain shadow region. Contrasting aerosol regime and hygroscopicity below and above cloud base. Four lognormal distributions based on observed aerosol spectra to constrain models.